Pengembangan Media Pembelajaran Matematika Pada Materi Bangun Ruang Sisi Datar dengan Konsep Gamifikasi - Muhammad Zakaria Isna Khauli; Nur Baiti Nasution; Sayyidatul Karimah (Universitas Veteran Bangun Nusantara, 2022)
In this study, we developed a learning media with the concept of gamification for plane geometry and examine the students’ responses to the media. Gamification is the concept of gamifying certain things to gain some engagement for that certain thing. In this study, we applied the gamification concept in a learning media for plane geometry. The media was made to fulfill scriteriarias of gamification which are challenges and levels. This study followed the research step of Borg the and Gall development research model which are: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design improvement, 6) product trial, and 7) product revision. The media itself was made using PowerPoint and was converted to ppsx fie. For knowing the validation and practicality, we used the Likert scale. The result of the validation test is 83.44% based on 8 validators and for practicality is 90.90% based on 34 students of MTs IN Banyurip Ageng. This study concluded that the mathematics learning media with the concept of gamification had sufficient results by the very valid and very practical criteria to be used as a media for plane geometry.